ASSISTENCE MEDIA LITERACY FOR YOUTH IN BENGKULU CITY - M. Ridho Syabibi; Rahmat Ramdhani; Poppy Damayanti (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
The background in this paper departs from observations and preliminary data regarding the use of social media by adolescents in Bengkulu City, which is known that they still do not have understanding or knowledge on aspects of Islamic religious norms and legal norms in media use. The purpose of this paper is to provide understanding, information and knowledge for youth in the use of social media, especially in the aspects of religious norms and applicable legal norms. The research method used was a qualitative approach with 30 informants who were determined through a techniquepurposeful sampling. The research results show that: 1). As many as 65% of informants have not used religious norms as a reference in media use; 2). As many as 60% of informants did not know the rules, regulations and legal impacts of media abuse.